2020
DOI: 10.1177/1756284820932483
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the efficacy and safety of second-line therapies for advanced hepatocellular carcinoma: a network meta-analysis of phase III trials

Abstract: Background: The prospect for targeted therapies in advanced hepatocellular carcinoma (HCC) has dramatically changed since several recent clinical trials have yielded promising results. The number of second-line therapies is increasing, though the consequent challenge is to consider differences between these interventions. This is a comparative investigation of presently approved second-line drugs for HCC based on findings from phase III randomized controlled trials. Methods: Data related to treatment efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…The results reinforce and build on those of a recent ITC that reported clinical equivalence of cabozantinib, ramucirumab and regorafenib with respect to OS in patients with serum AFP levels of 400 ng/mL or above [33] and of an NMA of available phase 3 trials of 2L agents for advanced HCC [34]. The NMA subgroup analysis of patients with AFP [ 400 ng/mL suggested that cabozantinib may significantly prolong PFS compared with ramucirumab (HR [95% CI], 0.59 [0.40, 0.88]), but it found no significant differences in OS estimates for cabozantinib, ramucirumab or regorafenib for patients with AFP [ 400 ng/mL.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results reinforce and build on those of a recent ITC that reported clinical equivalence of cabozantinib, ramucirumab and regorafenib with respect to OS in patients with serum AFP levels of 400 ng/mL or above [33] and of an NMA of available phase 3 trials of 2L agents for advanced HCC [34]. The NMA subgroup analysis of patients with AFP [ 400 ng/mL suggested that cabozantinib may significantly prolong PFS compared with ramucirumab (HR [95% CI], 0.59 [0.40, 0.88]), but it found no significant differences in OS estimates for cabozantinib, ramucirumab or regorafenib for patients with AFP [ 400 ng/mL.…”
Section: Discussionsupporting
confidence: 85%
“…Diarrhea was the most common AE reported for cabozantinib (54% of patients compared with 18% for ramucirumab), and peripheral edema was the most common for ramucirumab (36% of patients compared with 0% for cabozantinib). Overall, the authors considered the AEs in patients treated with ramucirumab to be relatively mild, with 36% of patients experiencing grade 3 or 4 AE rates compared with 68% of those treated with cabozantinib [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the current standard second-line HCC therapies, regorafenib appears to be the best choice in terms of OS. 7 However, given the low ORR and modest improvement in OS, a more effective second-line treatment is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding treatment-related adverse effects, good tolerance even in elderly patients was also reported with improvement of overall survival and quality of life [46]. In a network meta-analysis, Wang et al found that the efficacy of ramucirumab was comparable to regorafenib and cabozantinib in patients with AFP levels above 400 ng/mL, although the adverse effects were fewer with ramucirumab compared to regorafenib and cabozantinib [47]. In the present case, ramucirumab did not decrease tumor volume but dramatically reduced AFP level, and the tolerance was better for ramucirumab than for sorafenib and lenvatinib.…”
Section: Discussionmentioning
confidence: 99%